Analisis Penerapan Sistem Akuntansi Keuangan Daerah Dan Aktivitas Pengendalian Internal Terhadap Kualitas Laporan Keuangan Di Pemerintah Daerah : (Studi Kasus Pada Kantor Desa Sukoharjo, Kecamatan Sekampung, Lampung Timur) - Hendra Hafid Permadi; Hendri Hafid Permadi; Reza Rahmawati; Carmidah Carmidah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Regional government financial reports must present information that is relevant, reliable, comparable and easy to understand. This research aims to analyze the influence of the implementation of local government financial accounting systems and internal control activities on the quality of financial reports, both simultaneously and partially. This research is associative in nature. The sample used was 15 people in Sukoharjo Village, Sekampung District, East Lampung Regency, Garut using a saturated sampling method. The analysis used is path analysis because there is a relationship between independent variables. The research results show that the implementation of a regional financial accounting system has a positive but not significant influence on the quality of financial reports, while internal control has a negative influence which is also not significant on the quality of financial reports.